Fatigue life and mechanical behaviour of aluminium alloy aa6061 chips prepared by hot extrusion process - Rady, Mohammed Hussien (2019)
The global engineering activities nowadays are focusing on green and eco-friendly innovations. This has made the recycled materials a lucrative research sector. A study on fatigue life and mechanical behaviour of aluminium alloy aa6061 chips prepared by hot extrusion process was undertaken in this research. The fatigue, mechanical and physical properties of extruded products were investigated under varying preheating temperatures (PHT) of 450 °C, 500 °C, 550 °C and preheating times (PHTi) of 1 hr, 2 hrs, and 3 hrs respectively. From the Design of Experiments (DOE) principle, 11 samples (S1-S11) selected were sufficient to investigate the initial mechanical properties in which the optimum sample was later identified. This optimum sample was then heat treated to investigate the effect of heat treatment on the fatigue life. Comparisons were made with non-heat treated optimum sample and sample from the as-received material. The highest Ultimate Tensile Strength (UTS) was 174.62 MPa obtained at maximum PHT of 550 °C in sample 8. ANOVA indicate that PHT and PHTi parameters are significant over the UTS. For the microhardness, sample 5 is a profile extruded at 450 °C PHT and 1 hr PHTi demonstrated the maximum obtainable Vickers hardness of 55.69 HV. On top of that, the ANOVA showed that PHT contributes significantly to the microhardness while the PHTi parameter is not. In addition, the peak UTS of 340 MPa was observed in the heat treated extrudates, improved about 95 % compared to optimum UTS of 174.62 MPa in non-heat treated sample. While, the sample tested in as-received aluminium only resulted in 298 MPa. In fatigue analysis, the fatigue life endurance for three different cases was indicated by the S-N curve. The research successful demonstrated that the fatigue life endurance and mechanical properties of directly recycled aluminium alloy AA6061 chips can be improved about 28 % through the heat treatment. The preheating temperature was the key parameters that control the overall mechanical properties in direct recycling of aluminium alloy AA606 chips.